2021
DOI: 10.1038/s41598-021-84334-2
|View full text |Cite
|
Sign up to set email alerts
|

Ewe-lamb bond of experienced and inexperienced mothers undernourished during gestation

Abstract: The aims were to compare ewe-lamb behaviours between primiparous (PRI) and multiparous (MUL) undernourished grazing ewes at birth and at 3 months of age, and to determine if mothers’ parity affects milk yield and composition, and lambs’ body weight (BW). Food availability restricted the nutritional requirements from day 30 to day 143 of gestation. The MUL ewes had greater BW than the PRI during gestation, and their lambs tended to vocalize less frequently until their first suckle. PRI ewes both displayed a low… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Flushing is understood as the rapid increase in ovulation rate of ewes receiving a nutrient supplementation before mating. In this study nutrition (steaming up and supplementation) had improved ewes reproductive traits, where higher conception and lambing rate were notice in supplemented groups, these results agreed with [19][20][21][22][23][24][25][26][27][28][29][30][31] who reported that the highest lambing rates were in ewes that had been both flushed and steamed-up. Flushing and steaming-up had increased prolificacy as observed for Sudanese desert sheep by [32][33].…”
Section: Effect Of Supplementation Strategies and Parity Order On Rep...supporting
confidence: 84%
See 2 more Smart Citations
“…Flushing is understood as the rapid increase in ovulation rate of ewes receiving a nutrient supplementation before mating. In this study nutrition (steaming up and supplementation) had improved ewes reproductive traits, where higher conception and lambing rate were notice in supplemented groups, these results agreed with [19][20][21][22][23][24][25][26][27][28][29][30][31] who reported that the highest lambing rates were in ewes that had been both flushed and steamed-up. Flushing and steaming-up had increased prolificacy as observed for Sudanese desert sheep by [32][33].…”
Section: Effect Of Supplementation Strategies and Parity Order On Rep...supporting
confidence: 84%
“…Ewes with parity three where heavier during all period of gestation than ewes with parity one and two, this may be that older ewes had complete their body so they less weight loses, the current findings are similar to [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] they stated that there were positive change in body weight for ewes that lambing more than one times, also there were less weight lost after lambing and weaning. [29] reported that primiparous ewes had a lower body weight during gestation compared with multiparous which affects ewe's fertility. Contrast to these results [30] reported a greater effect of ewe live weight on reproductive performance in younger ewes than older ewes.…”
Section: Effect Of Feeding and Parity On Subsequent Body Weight Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ewe-lamb bond implies a close physical relationship during the first days after lambing (Ozella et al, 2022). Several factors may influence the strength of the attachment in lambs [e.g., sex, with female lambs showing a stronger attachment (Gaudin et al, 2015), birthweight (Menant et al, 2020)], and in ewes [e.g., parity (Dwyer and Lawrence, 2000;Freitas-de-Melo et al, 2021a), breed (Lawrence and Dwyer, 1999;Pickup and Dwyer, 2011), and temperament (Catherine and Alistair, 2000)]. In early postpartum, ewes have a strong preference for their lamb; but as the strength of the preference decreases, the preference of the lamb for the dam increases (Hernandez et al, 2009;Maldonado et al, 2015).…”
Section: Ewe-lamb Bond At Birth and During Lactationmentioning
confidence: 99%
“…Diversos fatores podem alterar a relação materno-filial de ovelhas e seus cordeiros, como o tempo de estabelecimento do primeiro contato, nutrição da ovelha, tipo de parto e ordem de parto, sendo que esta última influencia significativamente o desenvolvimento inicial dos cordeiros, uma vez que ovelhas primíparas acabam sendo mais estressadas durante esse início de relação materno-filial (SHEN-JIN et al, 2016;PETTIGREW et al, 2019;FREITAS-DE-MELO et al, 2021) A habilidade materna pode ser avaliada tradicionalmente pelo peso dos cordeiros desmamados por ovelha, mas também complementarmente pelo comportamento maternofilial. O comportamento da mãe próximo do cordeiro tem um grande efeito na sua sobrevivência neonatal, e pode também afetar o peso do cordeiro ao desmame e, assim, a produtividade da ovelha (RECH et al, 2008).…”
Section: Introductionunclassified